Thermoluminescent characterization and defect studies of graphite-rich media under high dose neutron exposure - Khandaker, Mayeen Uddin *; Nawi, S.N. Mat; Lam, S.E.; Sani, S.F. A.; Islam, Mohammad Amirul; Islam, M.A.; Naseer, K.A.; Osman, Hamid; Bradley, D.A. * (Elsevier, 2023)
Thermoluminescence (TL) materials have a broad variety of uses in various fields, such as clinical research, individual dosimetry, and environmental dosimetry, amongst others. However, the use of individual neutron dosimetry has been developing more aggressively lately. In this regard, present study establishes a relationship between the neutron dosage and the optical property changes of graphite-rich materials caused by high doses of neutron radiation. This has been done with the intention of developing a novel, graphite-based radiation dosimeter. Herein, the TL yield of commercially graphite-rich materials (i.e. graphite sheet, 2B and HB grade pencils) irradiated by neutron radiation with doses ranging from 250 Gy to 1500 Gy has been investigated. The samples were bombarded with thermal neutrons as well as a negligible amount of gamma rays, from the nuclear reactor TRIGA-II installed at the Bangladesh Atomic Energy Commission. The shape of the glow curves was observed to be independent of the given dosage, with the predominant TL dosimetric peak maintained within the region of 163 °C–168 °C for each sample. By studying the glow curves of the irradiated samples, some of the most well theoretical models and techniques were used to compute the kinetic parameters such as the order of kinetics (b), activation energy (E) or trap depth, frequency factor (s) or escape probability, and trap lifetime (τ). All of the samples were found to have a good linear response over the whole dosage range, with 2B grade of polymer pencil lead graphite (PPLGs) demonstrating a higher level of sensitivity than both HB grade and graphite sheet (GS) samples. Additionally, the level of sensitivity shown by each of them is highest at the lowest dosage that was given, and it decreases as the dose increases. Importantly, the phenomenon of dose-dependent structural modifications and internal annealing of defects has been observed by assessing the area of deconvoluted micro-Raman spectra of graphite-rich materials in high-frequency areas. This trend is consistent with the cyclical pattern reported in the intensity ratio of defect and graphite modes in previously investigated carbon-rich media. Such recurrent occurrences suggest the idea of employing Raman microspectroscopy as a radiation damage study tool for carbonaceous materials. The excellent responses of the key TL properties of the 2B grade pencil demonstrate its usefulness as a passive radiation dosimeter. As a consequence, the findings suggest that graphite-rich materials have the potential to be useful as a low-cost passive radiation dosimeter, with applications in radiotherapy and manufacturing.